The impact of histological variants of urothelial carcinoma on clinical outcomes following trimodality bladder-sparing chemoradiation - Kiltie, A; Browning, L (Elsevier, 2017)
Over 90% of bladder tumours are urothelial (transitional cell) carcinomas; most of the remainder are pure squamous cell carcinoma (3–5%) and adenocarcinoma (<2%). Invasive urothelial carcinoma (UC) shows diversity in its morphology in pure form, but divergent differentiation is also recognised within UC, most commonly squamous or glandular differentiation, in addition to the recognition of several specific variants. These UC variants are of interest clinically in terms of both prognosis and response to treatment. For example, some variants, such as lymphoepithelioma-like carcinoma, are important to recognise because of their apparently favourable response to chemotherapy. Others are associated with high-grade and locally advanced disease, lymph node metastases, more aggressive behaviour, and a poorer prognosis than for pure UC. While late stage at presentation may largely drive this outcome, some variants, such as sarcomatoid, are clearly aggressive with worse outcomes after adjusting for presentation stage.